Agro-industrial wastes as building insulation materials: A review and challenges for Euro-Mediterranean countries - Cintura, Eleonora (2022)
This study investigates the possibility of using agro-industrial wastes for building products, mainly focusing on their insulation properties. A classification of bio-wastes is provided, namely of the lignocellulosic ones and their features and properties are described. Information about three main topics is collected: world production and consumption of some crops already used as building materials, their chemical composition and their most studied properties. Since the considered materials are lignocellulosic and they have many common features, a com- parison is made. The aim is to have comparable information to support future research related to the production of eco-efficient indoor insulation boards. The result of this research is the choice of four different agro-industrial wastes produced in the Euro-Mediterranean Countries. This area was chosen as buildings typically have little or no insulation due to the regional mild climate; however, particularly with climate change, indoor hygrothermal comfort is poor. The collection of information allows some conclusions to be reached about the different bio- wastes already studied and identify gaps in the literature.